ADDRESSING THE ALARMING SURGE OF NAEGLERIA AND OTHER WATER-BORNE DISEASES IN KARACHI: A CALL FOR URGENT ACTION - Khan, Najam Ahmed; Anas Faheem; Hania Imtiaz; Muhammad Ismail; Sanila Mughal (Journal of Ayub Medical College Abbottabad, 2024)
Naegleria fowleri, a thermophilic, free-living organism causes a life-threatening condition called primary amoebic meningoencephalitis (PAM). Naegleria thrives in warm freshwater but the rising number of cases in Karachi has raised concerns about the quality of the city’s domestic water supply. Pakistan has dealt with numerous healthcare burdens in the past, including outbreaks of diseases such as diphtheria, and cholera, and is persistently dealing with the challenge of polio. Moreover, bacterial contamination and improper water infrastructure pose a significant public health risk to several other water-borne diseases, prevalent in the city. Furthermore, the surge in cases of Naegleria adds to these ongoing health concerns. This brain-eating amoeba has the potential to spread beyond its current location, posing a significant threat to the nation’s healthcare system. While the world is struggling to find an effective treatment for PAM, implementing preventive measures to improve water management, and surveillance can save lives and lessen the burden. The addition of chlorine to the water supply of the city by KWSB is a crucial step toward keeping this infection under control.